Employing dark matter and phantom-like fluids to alleviate the Hubble tension - Silva, Dêivid Rodrigo da (2023)
In this doctoral thesis, I investigate how the decay of a very heavy particle into dark matter and photons (or neutrinos) can alleviate the Hubble tension, that is, it can reconcile the value of the Hubble constant (H0) measured through the analysis of the cosmic microwave background (CMB) radiation with the measurements obtained in regions of the universe with low redshift. I show that by adopting the standard cosmological model, ΛCDM, this mechanism is unable to completely remove the tension, resulting in only a small reduction between the measurements of H0. However, in a universe with a phantom-like fluid, the decay adds enough radiation to the point where CMB measurements allow for H0 within the range of 70−74 km s−1 Mpc−1, which would completely eliminate the tension. I also use constraints from BBN to show that many of the important results of the standard cosmology are preserved, which prevents the model from being phenomenologically excluded.